2005
DOI: 10.1148/radiol.2373041380
|View full text |Cite
|
Sign up to set email alerts
|

T Staging of Gastric Cancer: Role of Multi–Detector Row CT

Abstract: Multi-detector row CT scanning of patients with gastric cancer gave 93% accuracy in the assessment of serosal invasion in patients with gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
1
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 21 publications
7
72
1
10
Order By: Relevance
“…For diagnoses of serosal invasion, MDCT findings were also considered [10]. A classification of cT4a was made when all layers of the gastric wall were visible on MDCT, indicating hypertrophy of the entire gastric wall and irregularities in the surrounding fatty tissue structures.…”
Section: Criteria For Determining the Preoperative Tumor Depthmentioning
confidence: 99%
See 1 more Smart Citation
“…For diagnoses of serosal invasion, MDCT findings were also considered [10]. A classification of cT4a was made when all layers of the gastric wall were visible on MDCT, indicating hypertrophy of the entire gastric wall and irregularities in the surrounding fatty tissue structures.…”
Section: Criteria For Determining the Preoperative Tumor Depthmentioning
confidence: 99%
“…With advancements in endoscopy [8], endoscopic ultrasonography [9], and multidetector computed tomography (MDCT) [10], several techniques have been established that provide satisfactory diagnostic data regarding the appropriate depth of invasion. A previous study regarding LN evaluation reported the improved diagnostic accuracy of MDCT [11].…”
Section: Introductionmentioning
confidence: 99%
“…Overall TNM staging results for each technique (AUS, CT, MRI, and PET) are presented in Tables 1, 2 [23,24,27,28,34,38,39,47,48,[53][54][55]58], to determine whether the use of more detector rows to capture images translated into better pre-operative staging performances (Table 6). Overall, CT scanners with C4 detectors had significantly better T staging performances compared to CT scanners with \4 detectors.…”
Section: Performance Characteristics Of Pre-operative Imaging Studiesmentioning
confidence: 99%
“…However, detector number did not significantly affect N or M staging performances. We compared the pooled TNM performance characteristics of CT scanners using traditional single plane axial images [25, 28-35, 37, 38, 40-42, 46, 49, 52, 57-59] with scanners using multi-planar reformatted (MPR) images [23,24,27,28,34,38,39,44,47,48,[53][54][55][56]58], to determine whether the addition of multiple image planes translated into better pre-operative staging performances (Table 6). Overall, CT scanners using MPR images had significantly better T staging performances compared to Pre-operative TNM staging S11 Data presented as pooled means ± standard error of all studies within a given category using the inverse variance method.…”
Section: Performance Characteristics Of Pre-operative Imaging Studiesmentioning
confidence: 99%
“…Its accuracy has constantly improved, for detecting both the invasion of gastric wall, ranging from 69 to 89 % [11][12][13], and nodal involvement, ranging from 69 to 92 % [14,15]. Nevertheless, MDCT involves the use of ionizing radiation and cannot adequately differentiate all the gastric wall layers.…”
Section: Introductionmentioning
confidence: 99%